Nutrition knowledge and customers perception towards kafeteria sihat program in Kota Kinabalu public healthcare foodservice - Aizul Azri Azizan; Dg. Khairunisa Ahmad Sapawi; Cheah, Yuen Kuan (BIMP-EAGA Unit for Tourism Development (BE-UTD), 2016)
Ministry of Health has launched Kafeteria Sihat all public hospital in Malaysia to educate people and intervention of health promotion. This research focuses on nutrition knowledge of customers and their perception towards Kafeteria Sihat on the aspects of food and drinks quality. Using convenience sampling, 4 public healthcare institution were choose and identified as nutrition knowledge and perceptions among customers as predictors of Kafeteria Sihat efficiency for its purpose of establishment. Customer‘s perception on healthy food categories showed the way of serving food with gravy separately and food prepared with low-fat milk were the most preferred (45.9%). However, customers have responded neutral about the level of salty foods (38.8%), the diversity of healthy drinks (39.9%) and healthy (39.9%) were sold in the Kafeteria Sihat and beverages made with low-fat dairy such as teh tarik (39.3%). However, the result reveals on healthy quality categories, the "food seem less oily" (36.9%) which gives an indication that the perception on food sold were oily and fatty foods. Most customers agree that the nutrition information should be provided in the Kafeteria Sihat (52.5%) and it gives awareness to the style of eating healthy (54.6%) while the poster gives information to the customers onnutrition (54.9%). Calorie labeling on food is considered as a good reference source (54.9%) and nutritional information displayed on Kafeteria Sihat is easy to understand (54.4%). Nutritional knowledge of customers Kafeteria Sihat considered being very good. The findings of this research could be useful for the public healthcare authorities to consider the efficiency of the implementation of Kafeteria Sihat and improve the intervention program for health promotion.